Sistemas de ejercicios de velocidad y aceleración en el cambio de dirección en futbolistas. - Aguirre Bravo, Anthony Alexander (2024)
The present research is carried out in order to improve the change of direction in soccer players of the Cantonal Sports League of Chambo sub-12, 15, and 16, the proposal includes specific training sessions addressing strength, speed, fast and explosive strength. The importance of physical abilities, periodic pre-post evaluation and specific training in football was highlighted. In addition, due to the relevance of determining factors such as plyometrics and power. Evaluation in football players is presented as a continuous and dynamic process. The importance of planning and evaluation in youth football is underlined. The relationship between motor tests and assessed factors is examined in detail. Specific training in football is divided into general and specific preparation, with a focus on tactics. The importance of injury prevention and the strengthening of physical capabilities is highlighted, with fundamental aspects for the integral development and optimal performance of soccer players, where a quasi-experimental methodology was used where we manipulated the variable through a system of speed and acceleration exercises, and a quantitative approach, since information was collected through the Illinois Agility Test. Where we observed the percentages in which the students were in a before and after, analyzing a positive increase in the average to good category by the footballers. Keywords: change of direction, speed, force, acceleration, planning